2011
DOI: 10.2460/javma.238.6.731
|View full text |Cite
|
Sign up to set email alerts
|

Interdog household aggression: 38 cases (2006–2007)

Abstract: Most treatment strategies were considered effective. Consistency and predictability of social interactions are essential in resolving interdog household aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…A significant difference in gender distribution was found between the group of dogs aggressive towards humans and the group of dogs aggressive towards other dogs, with a higher number of entire and spayed females in the latter group. In an earlier study, a prevalence of females was found in cases of intraspecific aggression [28]. Within the group of dogs aggressive towards other dogs, females and neutered females were also responsible for significantly more multiple aggression and group aggression.…”
Section: Discussionmentioning
confidence: 76%
“…A significant difference in gender distribution was found between the group of dogs aggressive towards humans and the group of dogs aggressive towards other dogs, with a higher number of entire and spayed females in the latter group. In an earlier study, a prevalence of females was found in cases of intraspecific aggression [28]. Within the group of dogs aggressive towards other dogs, females and neutered females were also responsible for significantly more multiple aggression and group aggression.…”
Section: Discussionmentioning
confidence: 76%
“…In other species, intra-group coalitional aggression is mainly related to challenges to established dominance rank, e.g., primates: [ 10 , 11 ] and domestic dogs: [ 42 ]. Pigs establish dominance relationships, and commonly use fierce reciprocal fights in this process, although these are rarely fatal [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A definitive explanation for these repeated findings (1, 2, 3, 15, 16) has not been proven. Speculation that trauma arises from inter-household aggression, dominance (20) and bite injuries caused by animals protecting their territory, being afraid, playing or protecting their property may reasonably explain why these injuries occur (21). …”
Section: Discussionmentioning
confidence: 99%